2014
DOI: 10.18632/oncotarget.2583
|View full text |Cite
|
Sign up to set email alerts
|

Combined inhibition of Chk1 and Wee1 as a new therapeutic strategy for mantle cell lymphoma

Abstract: Mantle cell lymphoma (MCL) is an aggressive, incurable disease, characterized by a deregulated cell cycle. Chk1 and Wee1 are main regulators of cell cycle progression and recent data on solid tumors suggest that simultaneous inhibition of these proteins has a strong synergistic cytotoxic effect. The effects of a Chk1 inhibitor (PF-00477736) and a Wee1 inhibitor (MK-1775) have been herein investigated in a large panel of mature B-cell lymphoma cell lines. We found that MCL cells were the most sensitive to the C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
59
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(66 citation statements)
references
References 48 publications
7
59
0
Order By: Relevance
“…In this cell line, despite an observed increased γH2AX, no decreased pCDK2 (Fig B) and less activity of the combination in terms of CI (0·77) was observed. A similar decrease in MYC protein levels after this drug combination was observed in MCL cell lines (Fig S4), while CHK1 protein expression remained unchanged (Chila et al , and data not shown). The striking decrease in MYC protein levels was not associated with a significant decrease in MYC mRNA (Fig C).…”
supporting
confidence: 74%
See 1 more Smart Citation
“…In this cell line, despite an observed increased γH2AX, no decreased pCDK2 (Fig B) and less activity of the combination in terms of CI (0·77) was observed. A similar decrease in MYC protein levels after this drug combination was observed in MCL cell lines (Fig S4), while CHK1 protein expression remained unchanged (Chila et al , and data not shown). The striking decrease in MYC protein levels was not associated with a significant decrease in MYC mRNA (Fig C).…”
supporting
confidence: 74%
“…CHK1 inhibitors are strongly synergistic with WEE1 inhibitors in many experimental models (Carrassa et al , ) and both kinase inhibitors are under early clinical investigation (Daud et al , ; Scagliotti et al , ). We had recently reported that DLBCL cell lines are more sensitive to the single inhibition of CHK1 and WEE1 inhibitors than epithelial cancer cell lines, albeit at a lesser extent than mantle cell lymphoma (MCL) cell lines (Chila et al , ). Here, we investigated the effects of CHK1 and WEE1 inhibition in a panel of DLBCL cell lines (Fig A) with different MYC status (Table S1).…”
mentioning
confidence: 99%
“…CoCaNet10 included conserved interactions among 59 TSGs and 23 drug targets; the more stringent CoCaNet2 captured the strongest conserved interactions, including those among DNA damage checkpoint, cell cycle checkpoint, topoisomerase, and chromatin remodeling genes. Inspection of these networks revealed 13 interactions that had been previously characterized in humans and 1 in yeast, including synthetic-sick relationships between CHEK1 or CHEK2 and WEE1 (Carrassa et al, 2012; Chila et al, 2015), which we recovered in both orientations (CHEK1/2 inhibitor with WEE1 knockdown and WEE1 inhibitor with CHEK1/2 knockdown). All remaining conserved interactions, representing the vast majority, were observed for the first time in either species (Figure 3C,D).…”
Section: Resultsmentioning
confidence: 86%
“…Since the primary clinical necessity in HPV(+) HNSCC currently is to safely deintensify treatment, dual inhibition with reduced doses may be a viable approach but as a new regimen would need to be carefully studied in clinical trials focusing on both toxicity and efficacy. A number of recent publications have reported synergistic effects when combining Chk1 and Wee1 inhibition in cells of various tumor entities in vitro and in xenograft models, and some also reported an activation of Chk1 upon Wee1 inhibition [25][26][27][28][29][30][31][32]. Dual inhibition induced replication arrest and DNA damage, apoptosis, premature mitosis and a reduction of proliferation and viability.…”
Section: Discussionmentioning
confidence: 97%